Antibiotic Treatment and Age Are Associated With Staphylococcus aureus Carriage Profiles During Persistence in the Airways of Cystic Fibrosis Patients - Westphal, Corinna; Görlich, Dennis; Kampmeier, Stefanie; Herzog, Susann; Braun, Nadja; Hitschke, Carina; Mellmann, Alexander; Peters, Georg; Kahl, Barbara C.; , Staphylococcal CF Study Group; Junge., Sibylle; Tümmler., Burkhard; et al. (Frontiers in Microbiology, 2020)
Background: Staphylococcus aureus is one of the most isolated pathogens from the airways of cystic fibrosis (CF) patients. There is a lack of information about the clonal nature of S. aureus cultured from CF patients and their impact on disease. We hypothesized that patients would differ in their clinical status depending on S. aureus clonal carriage profiles during persistence. Methods: During a 21-months prospective observational multicenter study [1], 3893 S. aureus isolates (nose, oropharynx and sputa) were cultured from 183 CF patients (16 German centers, 1 Austrian center) and subjected to spa-sequence typing to assess clonality. Data were associated to lung function, age, gender and antibiotic treatment by multivariate regression analysis. Results: 265 different spa-types were determined with 8 prevalent spa-types (isolated from more than 10 patients): t084, t091, t008, t015, t002 t012, t364, t056. We observed different carriage profiles of spa-types during the study period: patients being positive with a prevalent spa-type, only one, a dominant or related spa-type/s. Patients with more antibiotic cycles were more likely to be positive for only one spa-type (p=0.005), while older patients were more likely to have related (p=0.006) or dominant spa-types (p=0.026). Resistance of Methicillin-resistant S. aureus (2%) and also transmission of clones in centers were low. Conclusions: There was a significant association of antibiotic therapy and age on S. aureus clonal profiles in CF patients indicating that antibiotic therapy prevents acquisition of new clones, while during aging of patients with persisting S. aureus, dominant clones were selected and mutations in the spa-repeat region accumulated.